A pilot music group for young people attending a community Child and Adolescent Mental Health Service. (5th January 2015) - McDonald, J.; Codrea, A.; Gavin, B.
Abstract : Objective: There is a strong and growing body of evidence supporting the mental health benefits of music. With regard to Child and Adolescent Mental Health Services (CAMHS) there is a need for creative, child friendly approaches to improve rapport and promote engagement. This study was established as an exploratory pilot project to assess the feasibility of a running a music group within a CAMHS setting as well as any potential benefit to the mental health of a group of diagnostically heterogeneous young people attending the service. Methods: Five young people attending the out-patient clinic participated in a weekly music group over the course of 2 months. Feedback was obtained using a study specific questionnaire as well as baseline and follow-up Strengths and Difficulties Questionnaires. Results: The music group was described as an enjoyable experience in the clinic setting and young people identified benefits with regard to mood, self-confidence and social skills. Attendance at appointments within the clinic was good for the duration of the group, suggesting a benefit in encouraging engagement. Conclusions: A music group is a welcome intervention in a CAMHS setting with potential positive benefits for both the service and service users. Further work is needed to establish specific mental health benefits of music-based interventions in young people with mental health difficulties.